THE CHANGE OF PREVALENCE OF XEROPHTHALMIA ON LOMBOK, SEPTEMBER 1977 - SEPTEMBER 1983 - Ignatius Tarwotjo; Robert Tilden; Farida Farida; Atmarita Atmarita; robert Grosse; Alfred Sommer; Barbara Perry; Kathleen Richlen-Tilden (Persagi, 1989)
Berdasarkan data